COMPARISON OF EFFICACY OF NEURAL THERAPY AND PHYSICAL THERAPY IN CHRONIC LOW BACK PAIN - Atalay, Nilgun Simsir; Sahin, Fusun; Atalay, Ali; Akkaya, Nuray (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The aim of this prospective study was to evaluate the effects of neural therapy, and physical therapy on level of pain, disability, quality of life, and psychological status in patients with chronic low back pain. Patients admitted to the physical therapy and rehabilitation outpatient clinic with the complaint of low back pain of at least 3 months duration. Group 1 (n=27), physical therapy (PT, hotpack, ultrasound, TENS 15 sessions), group 2 (n=33), neural therapy (NT, 1:1 mixture of 20 mg/mL Lidocaine HCl (Jetokain simplex®) and saline for 5 sessions. For pain, Visual Analogue Scale (VAS), for disability Roland Morris Disability Questionnaire (RMDQ), for quality-of-life Nottingham-Health-Profile (NHP), for depression, and anxiety, Hospital Anxiety-Depression Scale (HADS) were used before and after The aim of this prospective study was to evaluate the effects of neural therapy, and physical therapy on level of pain, disability, quality of life, and psychological status in patients with chronic low back pain. Patients admitted to the physical therapy and rehabilitation outpatient clinic with the complaint of low back pain of at least 3 months duration. Group 1 (n=27), physical therapy (PT, hotpack, ultrasound, TENS 15 sessions), group 2 (n=33), neural therapy (NT, 1:1 mixture of 20 mg/mL Lidocaine HCl (Jetokain simplex®) and saline for 5 sessions. For pain, Visual Analogue Scale (VAS), for disability Roland Morris Disability Questionnaire (RMDQ), for quality-of-life Nottingham-Health-Profile (NHP), for depression, and anxiety, Hospital Anxiety-Depression Scale (HADS) were used before and after he treatment. Mean age was 47.3±11.32 years, symptom time was 13.78±11.98 months. There were no differences for demographic variables between groups. Significant improvements were detected for VAS, RMDQ, NHP-Pain, NHP-Physical activity, HADS for both of two groups after treatment. In addition to these findings, significant improvements were found for NHP-Energy, NHP-Social isolation in NT group. The differences of pre- and post-treatment values of parameters were evaluated for each group. Although there were no differences for VAS, NHP-sleep, NHP-Emotional reaction, HADS between groups, RMDQ, NHP-Pain, NHP-Physical activity, NHP-Social isolation were higher in NT than PT before treatment, the improvements for these parameters were better in NT than PT. In conclusion both of NT and PT are effective on pain, function, quality of life, anxiety, and depression in patients with chronic low back pain.